Conventional endodontic treatment of primary molars using metronidazole as an intra-canal medicament: a pilot study. - (:unkn) unknown (My University, 2010)
This was to evaluate the clinical and radiographic outcomes of an antibacterial drug (Metronidazole, Nidazol, IE Ulagay Ilac A.S) application as an intra-canal medicament combined with pulpectomy in infected primary molar teeth. The study material consisted of data collected from children treated at the Dental School Dept. of Paediatric Dentistry in Marmara University between 2000 and 2004. Clinical and radiographic data were collected over 2 years from patients who had received a topical application of metronidazole in root canal dressing before a pulpectomy was completed. Clinical success parameters were: no abscess formation, no fistula, no pain and no pathologic mobility at treated teeth with metranidazole dressing. The overall success and failure rates were analysed. Radiographic diagnosis was standardized between investigators and intra and inter-rater reliability assessed. Both investigators read and evaluated all radiographs, after a comparison of results, a consensus was agreed upon for each result. All data were entered into an Excel format and SPSS 11.0 P < 0.05 were used for Windows and Chi-square for statistical analyses. There were 64 molars assessed for clinical and radiographic success. Considering the eruption times, success rate was 75% as determined by the last follow up clinically and radiographically according to predetermined success criteria. In the 64 molars, 4 cases demonstrated loss of the alveolar bone, 3 exhibited varying degrees of root resorptions on radiographic examination and 3 showed clinical pathologic mobility. Fistulae were observed in only 1 case and early loss was detected in 5 cases. These results suggest that main factors responsible for failure may be associated with uncertain mixing proportions of the metronidazole paste and inadequate maxillary restorations. But some modifications in preparing the paste could increase its efficacy.